2004
DOI: 10.1136/jme.2003.004325
|View full text |Cite
|
Sign up to set email alerts
|

Proceeding with clinical trials of animal to human organ transplantation: a way out of the dilemma

Abstract: The transplantation of porcine organs to humans could in the future be a solution to the worldwide organ shortage, but is to date still highly experimental. Further research on the potential effects of crossing the species barrier is essential before clinical application is acceptable. However, many crucial questions on efficacy and safety will ultimately only be answered by well designed and controlled solid organ xenotransplantation trials on humans. This paper is concerned with the question under which cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Xenotransplantation is ‘the practice of transplanting, implanting or infusing cells, tissues or organs from one species to another’ (Ravelingien et al 2002 , 92). It may involve internal or external xenogenic therapies 1 designed as a temporary bridging device or as a ‘final solution to end-stage organ failure’ (Boneva and Folks 2004 , 504).…”
Section: Introductionmentioning
confidence: 99%
“…Xenotransplantation is ‘the practice of transplanting, implanting or infusing cells, tissues or organs from one species to another’ (Ravelingien et al 2002 , 92). It may involve internal or external xenogenic therapies 1 designed as a temporary bridging device or as a ‘final solution to end-stage organ failure’ (Boneva and Folks 2004 , 504).…”
Section: Introductionmentioning
confidence: 99%
“…11 There is also the risk that any such infection may prove contagious and spread to affect other members of the community. 17 It has been suggested that the source animals for transplants could be bred and raised in isolation from other animals so as to be disease-free. 12 There is also some evidence that this change has been brought about by animals of different species being brought into regular, close proximity as a result of human agricultural practices.…”
Section: The Risk Of Xenozoonosismentioning
confidence: 99%
“…16 Researchers are also developing techniques to try to eliminate or at least reduce them. 17 It has been suggested that the source animals for transplants could be bred and raised in isolation from other animals so as to be disease-free. 18 Unfortunately, this technique will not protect recipients from infection by agents they come into contact with after the operation, nor will it eliminate the risk posed by the existence of porcine endogenous retroviruses (PERVs), which are present in the genetic code of the cells of all pigs.…”
Section: The Risk Of Xenozoonosismentioning
confidence: 99%
“…1 Such monitoring may even be extended to the sexual partners, friends, and family of recipients. 9 Mandatory surveillance such as this is ethically controversial, as doing this violates rights to individual privacy. Precedents, such as the Declaration of Helsinki and the Nuremberg trials declaration, ensure that participation in studies is entirely voluntary, not hurried, and exit from the study is the autonomous decision of each participant.…”
Section: Ethical Considerationsmentioning
confidence: 99%